The Effect of Local Government Size, Regional Dependency and Regional Expenditure on Internet Financial Reporting (IFR) in Indonesian Provinces in 2019-2023 - Fitria, Elsa; Dwitayanti, Yevi; Aryani, Yuli Antina (Dinasti Publisher, 2025)
The purpose of this study is to assess the effect of local government scale, regional dependency, and regional expenditure on Internet Financial Reporting (IFR) in provincial governments in Indonesia during the 2019-2023 period. This research adopts a quantitative approach using secondary data obtained from the official websites of the Indonesian Supreme Audit Agency (BPK) and the Indonesian Central Bureau of Statistics (BPS). The sample consists of 34 provincial governments that consistently publish financial reports online, resulting in a total of 170 panel data observations. The analysis was conducted using panel data regression with the EViews 12 software. The results show that local government size has a positive and significant effect on IFR, regional dependence has a negative and significant effect on IFR, while regional expenditure does not have a significant effect. Simultaneously, the three independent variables have a significant influence on IFR. These findings imply that financial transparency through IFR is influenced by the structural and fiscal characteristics of the region, but is not necessarily determined by the level of government expenditure.